Crossing barriers; restoring barriers? Filaggrin protein replacement takes a bow. - IRVINE, ALAN (My University, 2014)
In this issue of the Journal, Stout and colleagues report a novel and creative approach to replacement of genetically determined absence or deficiency of epidermal proteins. While these early data are certainly interesting, further validation work is required to determine the utility of this approach in genodermatoses.
PUBLISHED
Keywords: filaggrin